Strategi Media Relations Praxis dalam Membangun Corporate Image Bank DBS Indonesia - Joses Karsten; Sinta Paramita (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2019)
Indonesia has now entered an era of rapid technological and internet development, which also requires the financial services industry to be able to follow it. This is indicated by the intense competition between banks in Indonesia that have started to develop their services in the form of digital banking. To overcome this problem, the thing done by Praxis as the PR Agency of Bank DBS Indonesia is to build an image as a bank that is not complicated in banking activities through a mission that is also a key message